Theories of everything and inexhaustibility of reality - Musso, Paolo (2015)
The question about the ultimate meaning of the world is as ancient as mankind. The novelty isthat, while during the previous centuries we were able to search for an answer only through art,mitology, philosophy and religion, nowadays we can search for it also by means of experimentalscience, especially cosmology and the so-called “Theory Of Everything” (TOE). The paradox isthat during this search science sometimes seems to contradict religion, especially christianism,from which nonetheless it was born. In the present paper we’ll see why this is not the case, andwhy no theory will ever be able to completely exhaust reality.